IITA's Rita celebrates International Youth Day 2022 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
Celebrating International Youth Day 2022, Rita explains how her interest in fighting hunger and malnutrition has led to her involvement in a research study that would help solve these problems that have plagued Africa's agriculture.